Cultural and linguistic security in the era of digitization (Journal of the College of Basic Education, 2023)
Culture is a general framework that brings together the people of the same nation, unites their thinking, and makes them defend their cultural components. Cultural security is formed from the heart's sense and awareness of belonging to a particular nation or people. Therefore, culture preserves the unity of its children, and cultural practices diversify and intersect with nations in light of the era of digitization, and through cultural identity, the nation proves itself. And its existence and fortify its self, cultural and historical identity. Cultural digitization, with its good deeds and good fruits, carries fears over the civilizations of nations and their gains, and confusion may be mixed with bombs, and the dye of power prevails over culture, and globalization spreads from its widest gates. The danger to our nation lies in its weakness in the areas of progress in its various aspects. From here, the subject of the study will be Arab cultural security, which deals with: linguistic security, equal culture, and globalization, which is the culture of normalization with control and hegemony. The study will present some examples in which the cultural security breach occurred, namely: social media, areas of life, and educational institutions.